Estrutura de famílias de pacientes com câncer em cuidados paliativos: estudo à luz do Modelo Calgary de Avaliação Familiar - Costa, Thaíza Ferreira da (2019)
Introduction: Palliative care is a therapeutic modality with an interdisciplinary approach consisting of a set of actions aimed at patients with life-threatening diseases, aiming to improve the quality of life and dignity of patients and their families. Objective: To evaluate the structure of families of cancer patients in palliative care, in the light of the Calgary Model. Methodology: This is a qualitative field research, developed in a philanthropic institution, located in the city of João Pessoa, Paraíba. The study included six families and cancer patients in palliative care. Structural assessment of the families of cancer patients under palliative care was performed. For data collection, the instruments recommended by the family assessment model used to delineate the internal and external structures of the family were used: genogram and ecomap. The empirical material was analyzed in light of the Calgary Family Assessment Model. As it is a research involving human beings, the requirements proposed by the National Health Council / Ministry of Health, through Resolution No. 466/2012, were considered. Results: the family evaluation of the six families studied allowed us to understand the main aspects related to the internal and external structures, as well as the family context. In addition to this aspect, the patients' bonds and their relationships in the family nucleus and the environment where they are inserted were identified, presenting the support network and the reorganization of family dynamics after the illness of their family members. Conclusion: The Calgary Family Assessment Model can be applied to diagnose the family structure of patients in palliative care, especially those undergoing cancer treatment, aiming to improve care and quality of life of the patient and family.